Application of Cloud Computing in Modern Accounting Practices a Systematic Literature Review - Sarah Zettira Agam Darwis; Muchriana Muchran; Muh Ramly (Harmoni Economics: International Journal of Economics and Accounting, 2026)
This study explores the application of cloud computing in modern accounting practices through a systematic literature review. The rapid advancements in information technology have revolutionized accounting information systems, making processes more efficient, integrated, and responsive. Cloud computing allows real-time, remote access to financial data across devices, enhancing transaction processing, reporting, and overall accuracy. The reviewed literature highlights that cloud-based accounting improves operational efficiency by automating tasks, streamlining workflows, enabling cross-department collaboration, and reducing infrastructure and maintenance costs. It also leads to better financial data quality through continuous updates, standardized procedures, and improved audit trails. Strategically, cloud adoption strengthens accounting’s role as a business partner by providing faster, more relevant insights for planning, control, and performance evaluation. However, challenges persist, particularly regarding data security, privacy risks, regulatory compliance, and service disruptions. Additionally, human resource factors, such as digital skills, change management, and user acceptance, are critical to successful implementation. In conclusion, this study provides a conceptual overview of how cloud computing enhances modern accounting, emphasizing its benefits in improving efficiency and decision-making, while recognizing the challenges that need to be addressed for its sustainable adoption.